CHARACTERISTICS AND INTERVENTIONS TO IMPROVE SKILLS OF CHILDREN WITH HEARING IMPAIRMENT - Kusumasari Kartika Hima Darmayanti (UIN Raden Mas Said Surakarta, 2021)
This study aims to explain the characteristics, etiologies, identifications, impacts, interventions, and some factors that contribute to individuals and students with hearing impairment. By using qualitative approach from data obtained from books and journal articles, it is found that there are four characteristics of individuals with hearing impairment. Hearing impairment often occurs due to genetic and non-genetic factors, and appears when the babies are in the period of language development (prelingual deafness). For facilitating individuals with hearing impairment, there are two methods; they are methods of communication and education. Three studies were found to be associated with hearing impairment. This is a basic step of literature review that relates to hearing impairment, further studies can focus on the factors contributing to hearing impairment based on educational or social context.